Efektivitas Model Pembelajaran Problem Based Learning Berbasis STEM Terhadap Kemampuan Koneksi Matematis Siswa - Yanto Nuryanto; Ricki Yuliardi (Indo-MathEdu Intellectuals Journal, 2023)
The problem in this study is the low ability of students' mathematical connections. This study aims to determine the effectiveness of the Problem Based Learning model based on Science Technology Engineering Mathematics (STEM) on students' mathematical connection abilities. The method used in this study was quasi-experimental with the non-equivalent pretest-posttest control group design chosen. This research was conducted at Kuningan 3 Public Middle School in May 2023. The sample was taken by purposive sampling consisting of class VIII B (Experimental Class) and class VIII A (Control Class). The number of students in both classes is the same, namely 30 students, a total sample of 60 students. The results of hypothesis testing on the results of the posttest data concluded that there were differences in students' mathematical connection abilities after the STEM-based Problem Based Learning model was applied to the experimental class and conventional models to the control class. There was a significant increase in students' mathematical connection abilities in the experimental group compared to students' mathematical connection abilities in the control group. Student responses to the STEM-based problem-based learning model in the experimental class received a positive response with a very high interpretation of the questionnaire results, namely 79%.